Post-pandemic online learning in Indonesian Mathematics Education: The perception-achievement relationship - Djam'an, Nurwati; Samah, Norazrena Abu; Nasrullah, Nasrullah (International Journal of Didactic Mathematics in Distance Education, 2026)
The COVID-19 pandemic accelerated online learning adoption in higher education, yet its longitudinal impact on mathematics education remains underexplored. This study investigated how mathematics education students' perceptions of online learning evolved between pandemic and post-pandemic periods and examined the relationship between these perceptions and academic achievement. Using an ex post facto quantitative design, we surveyed 157 undergraduate students at the Department of Mathematics, Universitas Negeri Makassar, Indonesia. Participants were stratified into two cohorts: during-pandemic and post-pandemic learners. We assessed four dimensions—resilience, infrastructure support, learning activities, and instructor competence—using structured questionnaires, complemented by semi-structured interviews for depth. Independent t-tests and linear regression analyses were conducted. Results revealed significantly more favorable perceptions among post-pandemic students, particularly regarding confidence, infrastructure adequacy, and interactive engagement. Students valued flexibility, access to materials, and opportunities for self-regulated learning. However, persistent challenges included comprehension difficulties and concerns about assessment fairness. Linear regression analysis indicated a statistically significant but weak positive relationship between perceptions and GPA (R²=.05), suggesting that while perception influences academic performance, it explains only 5% of achievement variance. These findings highlight that improvements in digital infrastructure and instructor competence enhanced student engagement, yet pedagogical strategies for conceptual understanding and authentic assessment require further development. The study contributes to understanding the evolution of online learning effectiveness beyond crisis contexts and underscores the importance of sustained investment in blended learning environments for mathematics education.